Application of Fiscal Reconciliation Towards Corporate Income Tax Calculations in Quality Fried Chicken Financial Reports - Emilda Kadriyani; Mislinawati; Muhammad Abthahi; Ramadhan, Rizki; M. Akmal (PT. Karya Inovatif Nusantara, 2025)
The purpose of research is to determine the application of Fiscal Reconciliation to the calculation of Corporate Income Tax in the financial statements of Quality Fried Chicken Banda Aceh. This topic was chosen because tax reconciliation is an important part of business tax reporting. The data used in this study are quantitative and qualitative. The data source used in this study is primary data. The results of this study indicate that Quality Fried Chicken Banda Aceh does not prepare its financial statements completely in accordance with Law Number 36 of 2008 concerning Income Tax. This is evidenced by several expense accounts that have not been subject to tax adjustments in the company's financial statements. Quality Fried Chicken Banda Aceh still does not have good evidence. Quality Fried Chicken Banda Aceh must know, understand and follow the development of taxation in Indonesia. Quality Fried Chicken Banda Aceh must also have good records in case of problems or events that are detrimental to the business.